Meet the phallic lecturer: early career research in a neoliberal imaginary - McKnight, Lucinda (Gender and education, 2020)
This article introduces the concept of the phallic lecturer, a spectral figure negotiated in the early stages of a research career in education, when the relative freedom of doctoral study morphs into compliance with institutional demands. Awareness of the dominance of the phallic in education emerges from reading curriculum theorist Madeleine Grumet, feminist philosopher Judith Butler and academic Judith Baxter, whose feminist poststructuralist discourse analysis offers ways to engage with the addresses and imperatives of phallicism that move beyond traditional, masculinist discourse analysis. The article expands an initial study of how secondary teachers both comply with and subvert curricula and shifts to the pedagogical addresses of university learning management systems, as they call gendered subjectivities into being, interpellating junior academics as shining lights or failed subjects. These concepts are offered to other researchers seeking to speak back to the common sense demands of neoliberalism that prosthetically structure work in higher education.